2014
DOI: 10.1371/journal.pgen.1004088
|View full text |Cite
|
Sign up to set email alerts
|

X Chromosome Control of Meiotic Chromosome Synapsis in Mouse Inter-Subspecific Hybrids

Abstract: Hybrid sterility (HS) belongs to reproductive isolation barriers that safeguard the integrity of species in statu nascendi. Although hybrid sterility occurs almost universally among animal and plant species, most of our current knowledge comes from the classical genetic studies on Drosophila interspecific crosses or introgressions. With the house mouse subspecies Mus m. musculus and Mus m. domesticus as a model, new research tools have become available for studies of the molecular mechanisms and genetic networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
157
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(167 citation statements)
references
References 65 publications
10
157
0
Order By: Relevance
“…This violation results in an undue number of incompatibilities partitioned as shared between the crosses from the X chromosome. Our findings should motivate higher-resolution mapping of X-linked incompatibilities in house mice, as has been achieved for F 1 hybrid male sterility between musculus and domesticus (Bhattacharyya et al 2014).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…This violation results in an undue number of incompatibilities partitioned as shared between the crosses from the X chromosome. Our findings should motivate higher-resolution mapping of X-linked incompatibilities in house mice, as has been achieved for F 1 hybrid male sterility between musculus and domesticus (Bhattacharyya et al 2014).…”
Section: Discussionmentioning
confidence: 55%
“…One explanation for this result is that the X chromosome contains more shared incompatibilities than the autosomes, and the PhyloQTL approach offers higher power than the heuristic method to detect these loci. The X chromosome confers hybrid male sterility between domesticus and musculus through complex regulatory mechanisms that remain unclear (Storchová et al 2004;Good et al 2008bGood et al , 2010Oka et al 2010;Campbell et al 2013;Turner et al 2014;Bhattacharyya et al 2014;Oka and Shiroishi 2014). It is possible that incompatibilities involving the X chromosome differ from purely autosomal interactions in some way that affects the snowball prediction.…”
Section: Discussionmentioning
confidence: 99%
“…One quantitative prediction of our model is that shorter chromosomes, which will acquire fewer DSBs, will be disproportionately affected by heterology at DSB sites, as the requirement for "interhomolog repair"-competent DSBs is least likely to be fulfilled. Interhomolog DSB repair is required for synapsis, and, indeed, short chromosomes are particularly vulnerable to synaptic defects in both male and female progeny of PWDf × B6m mice (Bhattacharyya et al 2014). Almost 70% of DSBs in B6 × PWD mice appear to form at hot spots with at least two variant bases in the central 200 bp (1%) (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This model of hybrid sterility does not account for the asymmetry of the hybrid sterility phenotype in PWD × B6 reciprocal crosses; however, such asymmetry may be exclusively determined by the Hstx1/2 locus on chrX. The PWD allele of Hstx1/2 plays a key role in male hybrid sterility (Storchová et al 2004;Bhattacharyya et al 2014) and significantly reduces the recombination rate relative to the B6 allele of Hstx1/2 (Bhattacharyya 2013). This does not appear to manifest as fewer meiotic DSBs in sterile as compared with fertile hybrids (Bhattacharyya 2013) but may act downstream from DSB formation to reduce the likelihood of a crossover-competent DSB on each chromosome.…”
Section: Discussionmentioning
confidence: 99%
“…F1 hybrid males from the reciprocal cross do not show sterility, suggesting that the M. m. musculus X chromosome is incompatible with dominant alleles of the M. m. domesticus autosomes (Flachs et al, 2012). Subsequent genetic studies showed that QTLs for male sterility, Hstx2 and Hst1, were located on the X chromosome (between 64.9 and 69.6 Mb) and chromosome 17, respectively (Gregorová et al, 1996;Trachtulec et al, 1997;Bhattacharyya et al, 2013Bhattacharyya et al, , 2014. Hst1 was mapped in the t-complex that occupies the proximal third of chromosome 17.…”
Section: The Large X Effect On Hybrid Sterilitymentioning
confidence: 99%